Gas production from different classes of methane hydrate deposits by the depressurization method. (23rd June 2019) - Yang, Mingjun; Gao, Yi; Zhou, Hang; Chen, Bingbing; Li, Yanghui
Summary: There are four primary classes of natural gas hydrate deposits in natural world. The differences between them are in the distribution of the methane hydrate, free gas, and free water layers. A reactor which the height was 120 mm and the inner diameter was 103 mm was used in hydrate formation and dissociation, and 17 thermocouples measured the distribution of temperature during the mining process. Different experimental means were applied to simulate three classes of methane hydrate deposits, in which water and glass beads filled in different orders. The hydrate samples were dissociated by depressurization, and the results showed no need to test a backpressure greater than 94% of the equilibrium pressure of methane hydrate. Class 1 sample's methane hydrate decomposition rate was slower than that of class 3 sample at the beginning of depressurization when backpressure was 2.3 and 2.6 MPa, but then, the opposite happened. The average dissociation rate decreased nearly linearly with the increase in backpressure for the class 1 samples. Abstract : Highlights Depressurization process for three classes of hydrate deposits was experimental studied. Hydrate reformation took place at 94% of hydrate equilibrium pressure. Gas recovery of the class 2 samples was the highest along the three deposit classes. Mass transfer and methane hydrate kinetics were the main influence factors on the initial process of methane hydrate dissociation.